RESPONAS OF GROWTH CHARACTERSTICS AND YIELD OF POTATO FERTILIZED WITH ORGANIC MATTER TO THE SPRAY OF FE AND ZN - Mhmood, Jawad Taha (Diyala Agricultural Sciences Journal, 2013)
A Field experiment was conducted in a private field at Al- Latyfia region ( 40 km. south Baghdad ) during spring season 2012, to study the effect of spraying of Fe ( 100 mg.l-1) and Zinc ( 60 mg.l-1) at different stages of potato growth on some vegetative growth characteristics and total tuber yield of potato fertilized with organic matter. Randomized Complete Block Design was adopted with three replications. Results showed that spray potato plants with Fe + Zn gave the highest values of plant branches ( 2.54 ), plant height ( 83.70 cm ), dry weight vegetative part ( 2.671 T.ha-1) and total tuber yield ( 34.48 T.ha-1). Spring potato plant at bulking growth stage gave highest values of plant branch ( 2.34), plant height ( 77.14 cm), dry weight part vegetative ( 2.291 T.ha-1) and total tuber yield ( 28.97 T.ha-1).